Penyimpangan Dana Desa Oleh Badan Permusyawaratan Desa Ditinjau Dari UU Nomor 6 Tahun 2014 Tentang Desa (Studi Kasus Desa Rawalo) - Rafsanjani, Nabiel Adib; Kartini, Ika Ariani (UMPurwokerto Law Review, 2024)
Abstract The village is a legal community unit that has territorial boundaries that are authorized to regulate and manage government affairs, the interests of the local community based on community initiatives. The Village Consultative Body is an institution whose authority and responsibility is as an institution which is the embodiment of democracy in the administration of village government. This study aims to determine whether the role of the Village Consultative Body is in accordance or not with Law Number 6 of 2014 concerning Villages, and the legal consequences and obstacles regarding the role of the BPD which are not in accordance with the Regulations of Banyumas Regency and Rawalo Village. Normative juridical research methods (normative legal research methods). The normative juridical research method is library law research which is carried out by examining library materials or secondary data. The results of the study show that the Village Consultative Body in its role in village government is not in accordance with Law Number 6 of 2014 concerning Villages. Because there are no reports showing that the village program is running smoothly, and there is a lack of involving the community in making village development plans. However, so far the Village Consultative Body has maximized it in order to create and improve community welfare. The form of misuse of village funds carried out by village officials, namely the Village Consultative Body according to the Village Law, is an act of misusing village finances and this is an act that is prohibited from being carried out by village officials. So the legal consequences for those who violate it are regulated in Article 18 paragraphs 1 and 2 of the Banyumas Regency Regional Regulation Number 11 of 2015 and explained in Article 16 of the Banyumas Regency Regional Regulation Number 11 of 2015. Keywords: village government, village consultative body, constitution, and local regulation Â  Abstrak Desa merupakan kesatuan masyarakat hukum yang memiliki batas wilayah yang berwenang untuk mengatur dan mengurus urusan pemerintahan, kepentingan masyarakat setempat berdasarkan prakarsa masyarakat. Badan Permusyawaratan Desa merupakan Lembaga yang dalan kewenangan dan tanggungjawabnya adalah sebagai Lembaga yang merupakan perwujudan demokrasi dalam penyelenggaraan pemerintahan desa. Penelitian ini bertujuan mengetahui apakah peran dari Badan Permusyawaratan Desa telah sesuai atau tidak dengan Undang-Undang Nomor 6 Tahun 2014 tentang Desa, dan akibat hukum serta hambatan mengenai peran BPD yang tidak sesuai dengan Peraturan Kabpuaten Banyumas dan Desa Rawalo. Metode penelitian yuridis normatif (metode penelitian hukum normatif). Metode penelitian yuridis normatif adalah penelitian hukum kepustakaan yang dilakukan dengan cara meneliti bahan-bahan purstaka atau data sekunder. Hasil penelitian menunjukan bahwa Badan Permusyawaratan Desa dalam perannya di pemerintahan desa belum sesuia dengan Undang-Undang Nomor 6 Tahun 2014 tentang Desa. Karena belum adanya laporan yang menunjukan bahwa program desa yang berjalan dengan lancar, dan kurangnya melibatkan masyarakat dalam membuat perancangan pembangunan desa. Namun selama ini Badan Permusyawaratan Desa sudah memaksimalkan demi menciptakan dan meningkatkan kesejahteraan masyarakat. Maka akibat hukum bagi yang melanggar diatur dalam Pasal 18 ayat 1 dan 2 Peraturan Daerah Kabupaten Banyumas Nomor 11 Tahun 2015 dan dijelaskan pada Pasal 16 Peraturan Daerah Kabupaten Banyumas Nomor 11 Tahun 2015. Kata kunci: pemerintahan desa, badan permusyawaratan desa, undang-undang dan perda